The Political Economy of Organisational Violence in Chinese Industry - Shou, Huisheng (2016)
"Organisational violence" involves wilful, illegal business behaviour that has the potential to harm workers, consumers, or the environment. We use a combined perspective from the fields of political economy and criminology to examine the incongruously high level of organisational violence among Chinese firms that exists despite robust efforts by the government to put forth regulatory laws that prohibit it. As the explanation for this incongruity, we assert two conditions that synergistically interact in a bidirectional relationship: 1) the complex legal structural barriers to effective enforcement against organisational violence caused by a politically biased and administratively fragmented Chinese political system, and 2) a socially disorganised business environment that does not recursively message the wrongfulness of organisational violence. The analysis rejects not only financial gain as a relevant factor in the commission of organisational violence but also other current pers